Flexural Behavior of Concrete Beams Reinforced for Shear with Steel Welded Wire Fabric - Younes, Abdulaziz M. (2021)
A Master of Science thesis in Civil Engineering by Abdulaziz M. Younes entitled, “Flexural Behavior of Concrete Beams Reinforced for Shear with Steel Welded Wire Fabric”, submitted in July 2021. Thesis advisor is Dr. Sami Tabsh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).